Pengembangan Multimedia Interaktif Mobile Learning Pengurusan Jenazah - Muhamad Tri Panunggal Aprianto; Saida Ulfa; Arafah Husna (Universitas Negeri Malang, 2021)
Abstract: Technology is expected to be used as one way to advance education in Indonesia. The purpose of developing interactive multimedia mobile learning body management is to produce products, which are attractive, interactive, growing interest and the learning spirit of students, learning without barriers and can play a role in the flexibility of learning more personalized and worthy of use. The Mobile learning interactive Multimedia product contains both dialogue, text, audio, animated video and images. The research methods used are research and development and on this development model used in the form of Model Lee & Owens. This research uses models from multimedia development according to Lee & Owens with three stages of completion, namely assessment/analysis, design and development. Development Results Interactive Multimedia Mobile Learning Body Management is a positive response and worth using. Abstrak: Teknologi diharapkan mampu dijadikan salah satu cara untuk memajukan Pendidikan di Indonesia. Tujuan pengembangan multimedia interaktif mobile learning pengurusan jenazah ini yaitu menghasilkan produk yang menarik, interaktif, menumbuhkan minat dan semangat belajar siswa, belajar tanpa hambatan dan dapat berperan dalam fleksibilitas belajar yang lebih personal dan layak digunakan. Produk Multimedia Interaktif mobile learning terdapat materi berupa dialog, teks, audio, video animasi dan gambar. Metode Penelitian yang digunakan yakni penelitian dan pengembangan dan pada pengembangan ini model yang digunakan berupa model Lee & Owens. Penelitian ini menggunakan model dari pengembangan multimedia menurut Lee & Owens dengan tiga tahap penyelesaian, yaitu assessment/analysis, design dan development. Hasil pengembangan Multimedia Interaktif Mobile Learning Pengurusan Jenazah ini mendapatkan respon positif serta layak digunakan.